Становление и развитие криминологического институционализма - Дремин, Виктор Николаевич; Дрьомін, Віктор Миколайович; Dremin, Viktor (My University, 2012)
The paper analyzes the crime from the standpoint of the institutional methodology. The formation and development of a new school in criminology is approached, which the author calls «criminological institutionalism». The subject of the institutional criminology is grounded.
Дремин В. Н. Становление и развитие криминологического институционализма / В. Н. Дремин // Наукові праці Національного університету «Одеська юридична академія» : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю. П. Аленін [та ін.] ; відпов. за вип. В. М. Дрьомін ; МОН України, НУ ОЮА. – Одеса : Юрид. л-ра, 2012. – Т. 11. – С. 374-388.
Keywords: преступность; социальные институты; институциональная криминология; криминологический институционализм; злочинність; соціальні інститути; інституційна кримінологія; кримінологічний інституціоналізм; crime; social institutions; institutional criminology; criminological institutionalism